PELATIHAN PENDIRIAN BANK SAMPAH KEPADA MASYARAKAT SUSUKAN SIROTO KECAMATAN UNGARAN TIMUR KABUPATEN SEMARANG - Atmanti, Hastarini Dwi; Rejekiningsih, Tri Wahyu; Muttaqin, Aris Anwaril; Majid, Rifaldi; Rinusara, Novita Mukti (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
This activity aims to promote clean living, raise community knowledge of environmental issues, and realize community welfare for the people living in Susukan Siroto, East Ungaran District, Semarang Regency, Central Java Province; in particular, the people living in RT 6 RW 2. The ability to oversee a waste bank devoted to inorganic waste is possessed by the residents. Community Development Practice is the approach taken, in which locals are asked to gain firsthand experience in managing a trash bank. Residents may now manage their waste as a result of this action. To sum up, citizens may manage their inorganic trash and place it in the waste bank, which will ultimately keep the environment clean and allow them to make extra money from the waste they place in the waste bank.